Shifting Meaning of Teacher Professional Education: Between Idealism and Reality at UIN K.H. Abdurrahman Wahid Pekalongan - Rif’iyati, Dian; Haryanto, Andung Dwi; Fauyan, Muchamad; Fajar, Muhammad (Jurnal Pendidikan Progresif, 2024)
Abstract: Shifting Meaning of Teacher Professional Education: Between Idealism and Reality at UIN K.H. Abdurrahman Wahid Pekalongan. Objectives: This research seeks to reveal the shift in meaning that occurs among Teacher Professional Education students in what positions and roles are carried out by UIN K.H. Abdurrahman Wahid Pekalongan as an educational institution and education personnel in creating professional teachers. Methods: Research The type of research used in this study is a qualitative method with a phenomenological approach. The informants for this research include the Chair and secretary of the Teacher Professional Education study program in the Faculty of Tarbiyah and Teacher Training, administrative staff, lecturers, and Professional Teacher Education students in positions in 2022 batches I, II, and III. Collection techniques include interviews, observation, documentation, and questionnaires. In qualitative data analysis, there are three activity streams: data condensation, data presentation, and conclusions. Findings: Shifts in the meaning of professional teacher education in positions include: competency not increasing, material orientation, minimal digital literacy among digital immigrant teachers, limited facilities and infrastructure, educational certificates as a tool for registering government employees with work agreements, and professional teacher allowances as the cause of increasing teacher divorces. Conclusion: The Role of Educational Institutions for Educational Personnel at UIN K.H. Abdurrahman Wahid Pekalongan in creating professional teachers through Teacher Professional Education is building synergy and cooperation with stakeholders, verifying and validating the physical files of in-service Teacher Professional Education students, optimizing the completeness of the implementation of the in-service Teacher Professional Education program, maximizing learning services, formulating effective strategies graduation of in-service Teacher Professional Education students, guaranteeing the quality of education, submitting reports on the implementation of in-service Teacher Professional Education, and strengthening the religious moderation ecosystem. Keywords: Shifting meaning, teacher professional education, idealism and reality.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202415